Directions and Foundations of Pope Francis’ Approach to Ecumenism - Sawa, Przemysław (Verbum Vitae, 2025)
The article presents an analysis of Francis’ numerous statements on the topic of ecumenism and attempts to synthesise papal thought in the key of directions, foundations and practical guidelines for the search for unity by contemporary Christians. The study of the source texts first helps to demonstrate the main areas of Francis’ ecumenism (including the motivation for a common path and theological dialogue, the focus on spiritual life and service to the world). The theological foundations of this service will then be recognised, above all the gift of grace, the ecclesiology of unity, starting from the source of baptism, the profession of faith and the perspective of holiness. Finally, the third part of the article is an attempt to synthesise Francis’ practical orientations and indications for ecumenism, including openness to the word of God and the Holy Spirit, evangelisation, awareness of imperfect unity, moving from the logic of “what I can teach” to “what I can learn,” response to the challenges of the world.